Tanmiyah Waqf al-Manāfi min Ajl al-Istiqlāliyah fī Majāli al-Iqtiṣād: Dirāsah fī Ma’had Tazakkā al-‘Aṣrī - Mulyono Jamal; Mohammad Hanief Sirajulhuda; Khurun'in Zahro; Muhammad Aunurrochim Mas'ad Saleh (Faculty of Sharia and Law Universitas Islam Negeri Walisongo Semarang, 2024)
Vol 33, No 1